Imaging Retinal Capillaries Using Ultrahigh-Resolution Optical Coherence Tomography and Adaptive Optics - Wang, Qiang (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. Ultrahigh-resolution optical coherence tomography (UHR-OCT) with adaptive optics (AO) provides micrometer-scale 3D resolution that is attractive for imaging the retinal microvasculature. Such imaging may be useful for early detection of pathologic changes as in diabetic retinopathy. Here the authors investigate this potential for detecting individual capillaries in healthy subjects. METHODS. UHR-AO-OCT volumes centered on the fovea were acquired from seven subjects (age range, 25–61 years) with three preselected with no foveal avascular zone (FAZ). Images were compared with entoptic diagrams using the capillaries at the rim of the FAZ. Methods of comparison were testing for the presence of a FAZ, noting distinct features in the capillary pattern, and measuring the size of the FAZ. Additional analysis included measurements of capillary diameter and depth range with retinal eccentricity. RESULTS. UHR-AO-OCT results are consistent with entoptic observations for all three methods of comparison. FAZ diameters measured by UHR-AO-OCT and entoptic imaging are strongly correlated (R(2) = 0.86). Average capillary diameter near the FAZ rim is 5.1 (4.6) ± 1.4 μm, with the value in parentheses accounting for axial image blur. This is consistent with histology (average, ∼4.7 μm). Depth range of the capillaries increases monotonically with eccentricity (0°–1.25°) and is larger and more variable for subjects without FAZ. CONCLUSIONS. UHR-AO-OCT permits observation of many of the capillaries proximal to the FAZ, including those of average size based on published histology. This supports the view that the vast majority of capillaries in the retina are likely detectable with UHR-AO-OCT.